1997
DOI: 10.1128/jb.179.12.4003-4012.1997
|View full text |Cite
|
Sign up to set email alerts
|

Comparative characterization of SecA from the alpha-subclass purple bacterium Rhodobacter capsulatus and Escherichia coli reveals differences in membrane and precursor specificity

Abstract: We have cloned the secA gene of the ␣-subclass purple bacterium Rhodobacter capsulatus, a close relative to the mitochondrial ancestor, and purified the protein after expression in Escherichia coli. R. capsulatus SecA contains 904 amino acids with 53% identity to E. coli and 54% identity to Caulobacter crescentus SecA. In contrast to the nearly equal partitioning of E. coli SecA between the cytosol and plasma membrane, R. capsulatus SecA is recovered predominantly from the membrane fraction. A SecA-deficient, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 74 publications
0
22
0
Order By: Relevance
“…T7 RNA polymerase-dependent in vitro expression of ccoH was achieved using plasmid pET19b-ccoH. Cell-free protein synthesis using [ 35 S]methionine and cysteine with R. capsulatus S-135 extracts was carried out for 30 min at 35°C as described previously (15,26,55). For cotranslational integration of in vitrosynthesized proteins into membranes, ICMs were added after 5 min of synthesis, and the reaction mixture was incubated for 25 min at 35°C.…”
Section: Methodsmentioning
confidence: 99%
“…T7 RNA polymerase-dependent in vitro expression of ccoH was achieved using plasmid pET19b-ccoH. Cell-free protein synthesis using [ 35 S]methionine and cysteine with R. capsulatus S-135 extracts was carried out for 30 min at 35°C as described previously (15,26,55). For cotranslational integration of in vitrosynthesized proteins into membranes, ICMs were added after 5 min of synthesis, and the reaction mixture was incubated for 25 min at 35°C.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro synthesis of cyt c 2 was performed using plasmid pC2P2.71, which carries the cycA gene under the control of both its own and the lac promoter. Cell-free protein synthesis using [ 35 S]methionine with R. capsulatus S-135 extracts was carried out for 30 min at 35°C as described previously (14,21,52). For cotranslational integration of in vitro-synthesized proteins into membranes, ICM were added after 5 min of synthesis, and the reaction mix was incubated for 25 min at 35°C.…”
Section: Methodsmentioning
confidence: 99%
“…The purification of SecA (Helde et al, 1997), SecB (Hoffschulte et al, 1994), and F 1 -ATPase (Mü ller et al, 1987) followed previously reported protocols. His-tagged Ffh (P48) was expressed from pDS12-48His6 in E. coli strain MC4100 containing the lac repressor-encoding pDMI,1 (Lentzen et al, 1994) and purified in a manner similar to that described by Lentzen and associates.…”
Section: Subfractionation Of Translation Productsmentioning
confidence: 99%
“…Inside-out inner membrane vesicles (INV) and translocation factors were added from the beginning. Gradient-purified inner membrane vesicles were obtained as described previously (Hoffschulte et al, 1994) and extracted with 6 M urea as detailed elsewhere (Helde et al, 1997).…”
Section: In Vitro Reactionsmentioning
confidence: 99%